2016
DOI: 10.1080/17415993.2016.1230857
|View full text |Cite
|
Sign up to set email alerts
|

Hetero-Diels–Alder reactions of hetaryl thiochalcones with acetylenic dienophiles

Abstract: Hetaryl-substituted thiochalcones react with acetylenic mono-and diesters in the THF solution in the presence of LiClO4 at 65°C to give, after 24h, 4H-thiopyran carboxylates and dicarboxylates, respectively, in moderate to good yields. The same reactions were performed also in the THF solution without a catalyst under microwave irradiation. In that case, the reaction time was reduced to three minutes and, in most cases, an improvement in the yield of the [4+2]-cycloadduct was observed. The reactions with methy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 29 publications
(18 reference statements)
0
16
0
Order By: Relevance
“…5-Chloro-10-hydroxy-1,4-anthraquinone ( 2d ) was obtained by treatment of quinizarine with thionyl chloride according to the protocol described in [27]. Thiochalcones 1a – d were prepared according to our protocol reported in an earlier publication [16]. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…5-Chloro-10-hydroxy-1,4-anthraquinone ( 2d ) was obtained by treatment of quinizarine with thionyl chloride according to the protocol described in [27]. Thiochalcones 1a – d were prepared according to our protocol reported in an earlier publication [16]. …”
Section: Methodsmentioning
confidence: 99%
“…Despite the fact that thiochalcones exist in solution as mixtures of dimers [1516], they enter into cycloaddition reactions not only as heterodienes [1719], but also as heterodipolarophiles [15]. In two recent publications we reported new thia-Diels–Alder reactions of aryl, hetaryl and ferrocenyl-substituted thiochalcones with acetylenic dienophiles, which lead to the corresponding 4 H -thiopyrans in a regioselective manner [16,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent publication we reported that acetylenic dipolarophiles react with thiochalcones 2 (Ar = Aryl or Hetaryl) yielding 4H-thiopyrans 3 in good to excellent yields, and in the case of methyl propiolate the reaction occurred with complete regioselectivity [6] (Scheme 1). Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
“…Scheme 1. Preparation of thiochalcones 2 and their regioselective hetero-Diels-Alder reactions with methyl propiolate [6].…”
Section: Introductionmentioning
confidence: 99%